Effects of Photobiomodulation Using Low-Level Laser Therapy on Alveolar Bone Repair - Rando, Renata Gonçalves; Buchaim, Daniela Vieira; Cola, Paula Cristina [UNESP]; Buchaim, Rogerio Leone (MDPI, 2023)
Alveolar bone repair is a complex and extremely important process, so that functions such as the mastication, occlusion and osseointegration of implants can be properly reestablished. Therefore, in order to optimize this process, many procedures have been used, such as grafting with biomaterials and the application of platelet-rich fibrin (PRF). Another method that has been studied is the use of photobiomodulation (PBM) with the use of low-level laser therapy (LLLT), which, through the absorption of photons by the tissue, triggers photochemical mechanisms in the cells so that they start to act in the search for homeostasis of the affected region. Therefore, the objective of this review was to analyze the use of LLLT as a possible auxiliary tool in the alveolar bone repair process. A search was carried out in scientific databases (PubMed/MEDLINE, Web of Science, Scopus and Cochrane) regarding the following descriptors: “low-level laser therapy AND alveolar bone repair” and “photobiomodulation AND alveolar bone repair”. Eighteen studies were selected for detailed analysis, after excluding duplicates and articles that did not meet predetermined inclusion or non-inclusion criteria. According to the studies, it has been seen that LLLT promotes the acceleration of alveolar repair due to the stimulation of ATP production, activation of transcription and growth factors, attenuation of the inflammatory process and induction of angiogenesis. These factors depend on the laser application protocol, and the Gallium Aluminum Arsenide—GaAlAs laser, with a wavelength of 830 nm, was the most used and, when applications of different energy densities were compared, the highest dosages showed themselves to be more efficient. Thus, it was possible to conclude that PBM with LLLT has beneficial effects on the alveolar bone repair process due to its ability to reduce pain, the inflammatory process, induce vascular sprouting and, consequently, accelerate the formation of a new bone matrix, favoring the maintenance or increase in height and/or thickness of the alveolar bone ridge.
Keywords: alveolar bone atrophy; alveolar bone loss; bone regeneration; low-level laser therapy; low-power laser therapy; photobiomodulation therapy